Foreign Insolvent Debtor: Some Essential Questions a Creditor is Facing in International Collective Insolvency Proceedings - Sladič, Jorg (LeXonomica, 2012)
Creditors in international trade are often faced with issues of an insolvent foreign debtor who often has property and assets in several states. In such a case creditors are faced with difficulties of international collective insolvency proceedings. The introductory parts of the article examines the standard questions like the question of a single, universal property of an individual or legal person and on the other hand the principles of territoriality and universality in public international law as far as the effects of foreign collective insolvency proceedings are concerned. The article then deals with issues of the centre of main interests as the point of contact and issues opened with the application of the lex concursus. Tuji insolventni dolžnik: nekaj bistvenih vprašanj, s katerimi se sooča upnik v mednarodnih insolvenčnih postopkih. V mednarodni trgovini se upniki dostikrat soočijo z vprašanjem stečaja svojih dolžnikov v tujini, ki imajo večkrat premoženje tudi v različnih državah. V takšnem primeru so upniki soočeni s težavnostjo mednarodnega stečaja. Uvodoma članek obdela standardna vprašanja, kot je na eni strani zasebnopravna teorija enotnosti premoženja in na drugi strani mednarodno pravni načeli teritorialnosti in univerzalnosti učinkov stečaja v tujini. Nato pa se ukvarja z vprašanjem središča glavnih interesov in pojmom lex concursus vmednarodnih stečajnih postopkih.